1953
DOI: 10.1017/s0021859600044944
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of gene-controlled sterility in bulls

Abstract: A study has been made of the relationships of sterile Friesian bulls manifesting ‘knobbed’ spermatozoa, and the conclusion drawn that the characteristic defect of the acrosome is due to an autosomal sexlimited recessive gene (kn).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…However, in the majority of reported cases the mode of inheritance is not clear because of the small numbers of animals or relatives of the affected animals which had been investigated. Donald & Hancock (1953) found the knobbed acrosomal defect in seventeen sterile Fresian bulls. These bulls were related, and the authors suggested that the condition was the result of a single autosomal recessive gene which has no effect on the females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the majority of reported cases the mode of inheritance is not clear because of the small numbers of animals or relatives of the affected animals which had been investigated. Donald & Hancock (1953) found the knobbed acrosomal defect in seventeen sterile Fresian bulls. These bulls were related, and the authors suggested that the condition was the result of a single autosomal recessive gene which has no effect on the females.…”
Section: Discussionmentioning
confidence: 99%
“…A 'knobbed' acrosomal defect has been described in the spermatozoa of bulls by Hancock (1953) and Blom & Birch-Andersen (1962) and in the spermatozoa from boars (Bane, 1961). An abnormality of the spermatozoa from some Guernsey bulls known as the 'decapitate defect' in which the head and tail become separated was shown to be associated with an ultrastructural abnormality in the neck region (Blom & Birch-Andersen, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…However, a common sensitivity to local conditions or to a n environmental agent may have led to expression of this lesion and recovery within the same time frame. Hereditary considerations apparently play a role in the expression of other sperm cell head defects, demonstrated most notably in the case of the knobbed acrosome defect in the bull (Donald and Hancock, 1953;Blom and Birch-Andersen, 1962) and the SME defect in the boar (Blom and Jensen, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal sperm morphology could not account for these findings. In Friesian bulls, abnormal development of acrosomes resulting in so-called "knobbed" sperm was implicated in sterility resulting from an autosomal sex-limited recessive gene influenced by local environmental conditions within the testes (41). A greater proportion of abnormal embryos might result from insemination in vitro than in vivo under conditions involving genetic aberrations and following cytogenetic evaluation insights to mechanisms of genetic toxicity, i.e., infertility, might be forthcoming.…”
Section: Uses and Potential Uses Of In Vitro Fertilizationmentioning
confidence: 99%